, 24.01.2020sabrinarasull1pe6s61

# Which graph represents an even function?

They are symmetric on the y axis
I don’t c any graphs?
First graph represents an even function

Step-by-step explanation:

For an even function we have f(x) = f(-x)

In the given graphs let us substitute values

In first graph

f(2) = 0

f(-2) = 0

So f(2) = f (-2)

Graph is even

In second graph

f(2) = 0

f(-2) = 4

So f(2) ≠ f (-2)

Graph is not even

First graph represents an even function

An even function is one symmetrical about the line x=0, or the y axis. A function is odd if f(-x)=-f(x). Starting from the back, since it's only on the right side of x=0, this clearly isn't right. Next, since we have the U shape on the right and not on the left, this isn't the answer we're looking for. After that, this seems right with the same design on both sides of x=0. The leftmost graph is not correct due to that x=1 and x=-1 are different - they should be the same.

The second graph to the left is therefore right

The second function represents an even function.

Step-by-step explanation:

A function g(x) is said to be even if g(x) = g(-x). All that is needed is to replace x with -x in each equation, simply it and assess whether the equation remains unchanged. If  the equation is identical to the original one then it is said to be even.

Step-by-step explanation:

The first graph (the parabola opening down) represents an even function, since this graph is symmetric with respect to the y-axis.

last graph

Step-by-step explanation:

Graphs of functions that are ODD, are symmetric about the origin.

Graphs of function that are EVEN, are symmetric about y-axis.

We need to figure out which one of the 4 are EVEN. So we take y-axis as the mirror and see both sides, LEFT and RIGHT and see i the points are symmetric or not.

Graph 1, 2, 3    not symmetric about y-axis

Graph 4    Definitely every point to left side of y-axis has a corresponding mirror point to the right of y-axis. So this is an EVEN FUNCTION.

Just took the test and the answer is C. The point is at (0,4) making it even.

The person before was wrong.

### Other questions on the subject: Mathematics

simplifying 5(x + -6) = 2(x + 3) reorder the terms: 5(-6 + x) = 2(x + 3) (-6 * 5 + x * 5) = 2(x + 3) (-30 + 5x) = 2(x + 3) reorder the terms: -30 + 5x = 2(3 + x) -30 + 5x = (3 *...Read More
Mathematics, 21.06.2019, lexybellx3